UV fluorescence, FTIR, and GC–MS analyses and resin fractionation procedures as indicators of the chemical treatability of olive mill wastewater. Issue 6 (1st February 2016) - Gursoy-Haksevenler, Betul Hande; Arslan-Alaton, Idil
Abstract: The organic matter content in original, untreated (COD = 150, 000 mg/L; TOC = 36, 000 mg/L; oil–grease = 8, 200 mg/L; total phenols = 3, 800 mg/L), and chemically treated olive mill wastewater was examined in detail by instrumental and analytical (resin fractionation) methods. For this purpose, two approaches were followed: (i) UV-fluorescence, FTIR, and GC–MS analyses as well as (ii) structural fractionation assessment employing XAD-8, XAD-4, AG-MP-50, and Duolite A-7 exchange resins to obtain hydrophobic-acidic, basic, neutral, and hydrophilic-acidic, basic, neutral fractions, respectively. Acid cracking (pH 2.0; T = 70°C), FeCl3 coagulation (pH 3.0; FeCl3 = 2, 500 mg/L) electrocoagulation with stainless steel electrodes (pH 2.0; T = 65°C; A = 50 mA/cm 2 ; t = 120 min), and the Fenton's reagent (pH 2.0; T = 65°C; 20 mM Fe 2+ : 200 mM H2 O2 ; t = 120 min) were selected for convenient chemical treatment of the effluent. Resin fractionation analyses of the original wastewater sample indicated that the major organic content composed of hydrophobic moieties (75–95%). The percent relative inhibition of the original wastewater was concentrated in the hydrophobic neutral fraction (100%). By employing instrumental analyses, several organic compounds could be identified. Relatively low molecular weight chemicals were qualified via GC–MS analysis, whereas FTIR results revealed an appreciable loss of aliphatic moieties together with an increase in aromatic structures.